X^(2)=4-6x

Simple and best practice solution for X^(2)=4-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X^(2)=4-6x equation:



X^(2)=4-6X
We move all terms to the left:
X^(2)-(4-6X)=0
We add all the numbers together, and all the variables
X^2-(-6X+4)=0
We get rid of parentheses
X^2+6X-4=0
a = 1; b = 6; c = -4;
Δ = b2-4ac
Δ = 62-4·1·(-4)
Δ = 52
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{52}=\sqrt{4*13}=\sqrt{4}*\sqrt{13}=2\sqrt{13}$
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(6)-2\sqrt{13}}{2*1}=\frac{-6-2\sqrt{13}}{2} $
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(6)+2\sqrt{13}}{2*1}=\frac{-6+2\sqrt{13}}{2} $

You can always share this solution

See similar equations:

| 15b+50=35 | | 17(5)^x=7(2)^x | | ((5x)/(2))+4=7x | | 4/3x-1+(2x+3)(2x-3)/12-(2x+3)2=2/3x-9x-3/6 | | 4/3x-1+(2x+3)(2x-3)/12-(2x+3)^2=2/3x-9x-3/6 | | 40x+10(1.5x)=1600 | | p+6p?5p=20 | | 4x^2-70x+150=0 | | 2x2+5x-8=0 | | 7x=3x+12=2x+5= | | 7x=3x+122x+5= | | 3/d+2=9 | | 50.?56+x=?12?23 | | 2*(x+8)=20 | | 22*x=226 | | 4n+12+3n=82 | | 2*(x+4)=14 | | 10=90(1/2)^x | | 17–x=9x= | | 5*(x-3)=15 | | 8*(x+2)=48 | | 4x+66=10x+12x= | | 12x-3x-36000=0 | | 0,5*(x-8)=5 | | 5*(x+4)=30 | | 44=2/3x | | n/20=3 | | 0.2x-1.7=0.6x-0.1 | | 13x2+28x+4=0 | | 0.4x-1.5=0.7x-0.6 | | n+28=96 | | 7b-6(b+1)-b=5(b-1)-5b | | 8y-3=-2 | | 3y-10=-9 | | X3-12x-16=0 | | (3x+12)/5-(x+4)/3=23/15 | | 5x²-25x+10=0 | | 3x+12/5-x+4/3=23/15 | | 12x+54=120 | | 2x=63?5x | | 2x+10/3-x+3/4=37/12 | | 0,5x/7+0,5x/3=1 | | 5p-p/5=24p/5+1 | | x/4+9x/10=-23/20 | | 1/3x+0.2x=16 | | (x/2/3)+(x/2/7)=1 | | 2m+10-5m=6(m+2)-9m | | 0.5x-3.9=-1.9 | | 5z+4/3-(-3z-5/2)=-z+43/6 | | 7(x+3)=-21 | | 7x+2-3x+1=8x+4-x+1 | | 4z+8=7 | | (3x/2)+(7x/2)=1 | | 3x+7x=1 | | 1=100e^-0.35N | | 3x+40+2x+6=88 | | P=-x-40x2+2,240x-17,000 | | 3+7=5x | | x^2+6x+6=-5 | | 5-7x=10-2x | | 2x+16=4× | | 160-(3x+x)=0 | | 160-(3x-x)=0 | | 5a+86=4a+24 | | 4t+8=39 |

Equations solver categories